1990
DOI: 10.7164/antibiotics.43.143
|View full text |Cite
|
Sign up to set email alerts
|

Probestin, a new inhibitor of aminopeptidase M, produced by Streptomyces azureus MH663-2F6. I. Taxonomy, production, isolation, physico-chemical properties and biological activities.

Abstract: Probestin has been isolated as part of a program designed to find microorganism-produced inhibitors of aminopeptidase Mfrom Streptomyces azureus MH663-2F6.It was purified by use of column chromatography of Amberlite XAD-4, silica gel, YMC-gel, Toyopearl HW-40, YMC D-ODS-5(HPLC) and then isolated as colorless powders. Probestin is competitive with the substrate, and the inhibition constant (Ki) of it was 1.9 x 10"8 m.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 8 publications
1
21
0
1
Order By: Relevance
“…Although H9 and HUT78 cells express neutral aminopeptidase activities equal to or higher than U937, respectively, only a minor fraction of the aminopeptidase activity in T cells really originates from the APN gene. This could be concluded from the lack of inhibition of the enzymatic activity by the antibody WM15, strongly decreasing APN activity [21] and the low inhibition of enzymatic activity by the APNspecific inhibitor probestin [22]. Summarizing these data, it could be concluded that only 5 20% of total neutral aminopeptidase activities in T cells represent membrane-bound APN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although H9 and HUT78 cells express neutral aminopeptidase activities equal to or higher than U937, respectively, only a minor fraction of the aminopeptidase activity in T cells really originates from the APN gene. This could be concluded from the lack of inhibition of the enzymatic activity by the antibody WM15, strongly decreasing APN activity [21] and the low inhibition of enzymatic activity by the APNspecific inhibitor probestin [22]. Summarizing these data, it could be concluded that only 5 20% of total neutral aminopeptidase activities in T cells represent membrane-bound APN.…”
Section: Discussionmentioning
confidence: 99%
“…All measurements were made in triplicate as previously described [13]. The presence of APN was detected using APN-specific effectors, such as the anti-CD 13 monoclonal antibody WMI5 [21] and the APN-specific inhibitor probestin [22].…”
Section: Enzymatic Assaymentioning
confidence: 99%
“…It is also present in phebestin (167), an inhibitor of aminopeptidase N [157], and in probestin (168) [158], an inhibitor of aminopeptidase M [159] (Figure 4.26 Ahoa (159) is present in the cyclic heptapeptide nostophycin (169) isolated from a cyanobacterium of the genus Nostoc [160], while Apoa/Ahmp (160) and its p-bromophenyl derivative Aboa (161) occur in theonegramide [161], the theonellamides A (170) and D (171) [17,18], and theopalauamide [162], which are bicyclic dodecapeptides isolated from marine sponges belonging to the genus Theonella (Figure 4.27).…”
Section: Biosynthesis Of B-amino Acids J139mentioning
confidence: 99%
“…Up to now, a quantity of APN inhibitors such as Bestatin, Probestin 8 , Amatatin 9 , Prebestin 8 , Lapstatin 10 , AHPA-Val 11 have been reported. The first APN inhibitor Bestatin was isolated from a culture filtrate of Streptomyces olivoreticuli in 1976 12 , and now generally used as the positive control in the assay of small molecule APN inhibitors.…”
Section: Introductionmentioning
confidence: 99%